Typical and atypical appearance of early‐onset Alzheimer's disease: A clinical, neuroimaging and neuropathological study. Issue 2 (17th January 2017) - Kawakatsu, Shinobu; Kobayashi, Ryota; Hayashi, Hiroshi
Abstract : The International Working Group (IWG) has classified Alzheimer's disease (AD) as two different types, the typical form and the atypical form, but clinicopathological studies of atypical AD are limited. Because atypical AD cases usually present with early‐onset dementia, we investigated 12 patients with early‐onset AD, including two patients with typical AD and 10 patients with atypical AD. Of these patients, six had the posterior variant, three had the frontal variant and one had the logopenic variant mixed with semantic dementia. We reported MRI, single‐photon emission CT and neuropathological findings in six representative cases. We also described a "left temporal variant" of AD presenting with transcortical cortical sensory aphasia, which has not been reported previously and is another subtype of the posterior variant of AD. We found a significant correlation between regional cerebral blood flow and counts of NFTs in the cerebral cortices. An atypical presentation with focal neuropsychological symptoms roughly correlated with the density of NFTs in the cerebral cortex and more directly related to spongiform changes in the superficial layers of these areas. In contrast, the distribution of amyloid depositions was diffuse and did not necessarily correlate with focal neuropsychological symptoms. Braak staging or ABC score is not necessarily appropriate to evaluate atypical AD, and instead, spongiform changes in addition to tau pathology in the association cortices better explain the diversity of atypical AD. Interestingly, another patient with a posterior variant of AD had a novel type of atypical plaque, which we referred to as "lucent plaque". They were recognizable with HE staining in the circumference and dystrophic neurites were abundant with Gallyas‐Braak staining. These plaques demonstrated intense immunoreactivity to both tau AT‐8 and amyloid β (Aβ), suggesting a peculiar coexistence pattern of amyloid and tau in these plaques. Clinicopathological studies of atypical AD will provide a new understanding of the pathophysiology of AD.